(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The art of national Makom, which is an integral part of our people’s cultural heritage, holds a special place in our spiritual life due to its ancient history, deep philosophical roots, unique artistic style, and rich creative traditions. This article provides methodological recommendations for the formation of singing qualifications based on Nasrullah’s singing in the discipline "Fundamentals of Makom Art," which is included in the curriculum for music education in higher education institutions, in accordance with the requirements of Presidential Decree No. PP-3391 dated November 17, 2017, "On Measures for the Further Development of the Uzbek National Art of Makom."